210Po production in the European DEMO fusion reactor. (29th August 2019) - Mertens, Merlijn A.J.; Fischer, Ulrich; Pereslavtsev, Pavel; Stieglitz, Robert; Noterdaeme, Jean-Marie; Cottenier, Stefaan
Abstract: The radionuclide inventory plays a central role in the safety of nuclear installations both during operation and their decommissioning. In nuclear fusion reactors using Pb–Li tritium breeding blankets, the undesired production of radiotoxic 210 Po is still an unresolved safety issue. In this work, neutron transport calculations and inventory calculations are combined to predict the 210 Po inventory in a DEMO fusion reactor using either a helium cooled lithium lead or a water cooled lithium lead breeding blanket. In order to guarantee that the environmental 210 Po release associated with an ex-vessel leak-of-PbLi accident remains below the no-evacuation limit, the 210 Po concentration in the Pb–Li should be kept below 1500 appt. It was found that no Pb–Li purification is required to keep the 210 Po concentration in DEMO below this limit. However, in case the Pb–Li makes direct contact with water, more volatile Po-containing (oxy-)hydroxides could form. If these species increase the 210 Po release rate by more than a factor of two, safety measures will be required. Therefore, 210 Po generation in DEMO does not pose a hazard in case of a regular ex-vessel leak-of-PbLi accident, unless possibly in case the Pb–Li makes contact with water.